2021
DOI: 10.1080/23311916.2020.1861731
|View full text |Cite
|
Sign up to set email alerts
|

Field monitoring and numerical analysis of ground deformation induced by tunnelling beneath an existing tunnel

Abstract: The main challenge of implementing and constructing a new tunnel is to monitor and mitigate ground surface disturbances that may affect existing structures. This paper analyses the soil deformations induced by tunnelling under an existing tunnel and the effect of these deformations on the existing tunnel. Both field data and numerical modelling are included in this study. Numerical modelling based on the finite element method is established to simulate the tunnelling process and the technique used in the shiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Most studies [3,27] investigated these issues for single tunnels; however, limited studies are available for twin tunnels using earth pressure balance (EPB) shield machines. In the recent numerical tunnelling analysis carried out by Islam and Iskander [28], the effect of geometric parameters and construction sequence on the SS was investigated using MIDAS GTS NX software 2021 (v1.1).…”
Section: Sand and Clay Shield Machinementioning
confidence: 99%
See 3 more Smart Citations
“…Most studies [3,27] investigated these issues for single tunnels; however, limited studies are available for twin tunnels using earth pressure balance (EPB) shield machines. In the recent numerical tunnelling analysis carried out by Islam and Iskander [28], the effect of geometric parameters and construction sequence on the SS was investigated using MIDAS GTS NX software 2021 (v1.1).…”
Section: Sand and Clay Shield Machinementioning
confidence: 99%
“…The interplay between the tunnel lining and the nearby soil can trigger certain adaptations and shifts in the ground, indirectly resulting in surface settlement. Numerous studies [3,24] have demonstrated that face pressure and grouting pressure are the two important contributors to the SS caused by mechanised tunnelling. Hence, in this study, these two parameters were considered to be part of the finite element analysis.…”
Section: Tunnel Boring Machine (Tbm) Operational Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…Xu et al [40] studied the influence of new tunnels with different excavation sequences and grouting reinforcement ranges on existing pipelines above. Using the finite element model, Nasser et al [41] analyzed the ground deformation caused by a new tunnel undercrossing an existing tunnel, and obtained some parameters to control the deformation. Xue and Zhang [42] studied the support pressure of the excavation face when a new tunnel crossed beneath an existing tunnel, and analyzed its influence on the surface settlement and segment deformation.…”
Section: Introductionmentioning
confidence: 99%